Komercjalizacja tacierzyństwa. Relacja ojca z dzieckiem na tle działań marketingowych - Janowicz, Kamil; Jasielska, Aleksandra (Człowiek i Społeczeństwo, 2021)
The last decades brought us dynamic changes in patterns of fatherhood. It is related both to expectations toward men, and their daily functioning itself. However, the role of a father is less often commercialized than the role of a mother. In line with that, commercials and marketing activities are less often addressed to fathers than to mothers. This paper is addressed to the potential grounds of this state of affairs, and the description of the new phenomenon – dadvertising. The possible manners of profiling marketing activities including fathers as primary recipients will be presented and discussed concerning findings of studies from the field of family psychology, sociology of the family, and a few existing studies aimed at commercials addressed to fathers. The abovementioned issues will be illustrated by examples of single commercials and marketing campaigns, in which protagonists or recipients were fathers.